Sujeito perceptivo e mundo em Merleau-Ponty - Marcus Sacrini A. Ferraz (DoisPontos, 2008)
In this article, we intend to show how Merleau-Ponty’s conception of the relations between the perceptual subject and the world changes in his works. In his book Phenomenology of Perception, published in 1945, Merleau-Ponty ascribes to such subject the capacity of adequately grasping the being of the world. However, in the beginning of the fifties, his analysis of psychologist Kurt Koffka’s works makes explicit some results which are incompatible with the ascription of such capacity to the subject. Finally, in The Visible and the Invisible (the philosopher’s final text, written during 1959-1961 and published posthumously), Merleau-Ponty acknowledges that the capacities of perceptually grasping the being of the world have limitations.